DISCOUNTED FEYNMAN KAC UNTUK MENCARI BENTUK PDP PADA PENENTUAN HARGA OPSI SAHAM KARYAWAN SETELAH VESTING PERIOD - Rudianto Artiono, (Matematika dan Sains, 2011)
One of the compensation form which can given by the business to employee was Opsi Saham Karyawan (OSK). It gave right to employee to buy a part of the business share at a period in future with the fixed value. In giving OSK, there are fitures to accommodate the needs of business and employee attitudes. The fitures used in determination of OSK with the Verr model are vesting period, exit rate, reload, and reset. Discounted Feynman Kac can be used to find the partial differential equation to determine the value of OSK after pass the vesting period.